Power tower must be executed from top to the bottom. Let 2^x=u and 3^x=v --> 2^v=3^u Take log: vlog(2)=ulog(3) (3^x)log(2)=(2^x)log(3) Divide by (3^x)log(3): (⅔)^x=[log(2)]/log(3) Again take log to get x: x=log[{log(2)}/log(3)]/[log(2)-log(3)]
Power tower must be executed from top to the bottom. Let 2^x=u and 3^x=v --> 2^v=3^u Take log: vlog(2)=ulog(3) (3^x)log(2)=(2^x)log(3) Divide by (3^x)log(3): (⅔)^x=[log(2)]/log(3) Again take log to get x: x=log[{log(2)}/log(3)]/[log(2)-log(3)]
Good efforts
🙏
Power tower must be executed from top to the bottom.
Let 2^x=u and 3^x=v --> 2^v=3^u
Take log: vlog(2)=ulog(3)
(3^x)log(2)=(2^x)log(3)
Divide by (3^x)log(3):
(⅔)^x=[log(2)]/log(3)
Again take log to get x:
x=log[{log(2)}/log(3)]/[log(2)-log(3)]
What is the difference between
2^2^3 and (2^2)^3
2^2^3=2^8=256
(2^2)^3=4^3=64
Or
(2^2)^3=2^(2*3)=2^6=64
🙏
Apply logerthms.
Power tower must be executed from top to the bottom.
Let 2^x=u and 3^x=v --> 2^v=3^u
Take log: vlog(2)=ulog(3)
(3^x)log(2)=(2^x)log(3)
Divide by (3^x)log(3):
(⅔)^x=[log(2)]/log(3)
Again take log to get x:
x=log[{log(2)}/log(3)]/[log(2)-log(3)]